2013
DOI: 10.1111/zsc.12018
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial phylogeography, contact zones and taxonomy of grass snakes (Natrix natrix,N. megalocephala)

Abstract: Grass snakes (Natrix natrix) represent one of the most widely distributed snake species of the Palaearctic region, ranging from the North African Maghreb region and the Iberian Peninsula through most of Europe and western Asia eastward to the region of Lake Baikal in Central Asia. Within N. natrix, up to 14 distinct subspecies are regarded as valid. In addition, some authors recognize big‐headed grass snakes from western Transcaucasia as a distinct species, N. megalocephala. Based on phylogenetic analyses of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
153
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(189 citation statements)
references
References 67 publications
9
153
1
1
Order By: Relevance
“…While thermophilic species retreated and lost habitat during glacial periods (e.g. Hewitt, 1999;Garcia-Porta et al, 2012;Kindler et al, 2013), cold temperate species expanded their distributional ranges, potentially connecting populations with the increase of suitable habitats (e.g. Fedorov et al, 2003;Kropf et al, 2003;Bannikova et al, 2010;Velo-Ant on et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While thermophilic species retreated and lost habitat during glacial periods (e.g. Hewitt, 1999;Garcia-Porta et al, 2012;Kindler et al, 2013), cold temperate species expanded their distributional ranges, potentially connecting populations with the increase of suitable habitats (e.g. Fedorov et al, 2003;Kropf et al, 2003;Bannikova et al, 2010;Velo-Ant on et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This hybrid zone lies at the meeting point of the two taxa with long independent evolutionary history recolonizing Europe from different glacial refugia. Anguis fragilis might have expanded to western Europe from a glacial refugium located in the north-western Balkans (Gvozdik et al, 2010) similarly to Natrix natrix lineage 3 (Kindler et al, 2013), while A. colchica populations most probably survived the last glaciations in southern Caspian, Caucasian, and presumably Carpathian refugia, recolonizing Eastern and Northern Europe (Gvozdik et al, 2010). This pattem is similar to expansion of Emys orbicularis lineage II presented by Fritz et al (2007).…”
mentioning
confidence: 97%
“…1). Using mito chondrial DNA sequences, Kindler et al (2013) demonstrated that grass snakes are genetically much differentiated. However, the current sub species classification does not match genetic differentiation and needs revision.…”
mentioning
confidence: 99%